An Analysis of Spatial Configuration at Qal’eh Dokhtar, Kerman Using the Space Syntax Technique - Sare Tahmasbizade; Maryam Mohammadi; Saeed Amirhajloo (Iranian Journal of Archaeological Studies, 2023)
Forts are among the evidences that are central to understanding administrative-political sovereignty. Qal’ehDokhtar is a fort with a special position in Kerman’s history thanks to the measures its builders had taken regardingits approach and security. The present contribution aimed to analyze and expound upon the spatial relationships inQal’eh Dokhtar’s architecture using the space syntax technique. The dataset deriving from the field surveys andhistorical texts was analyzed in Depthmap software. The results showed that the so-called “ruler’s residence” hadthe highest spatial depth, and its difficult access furnished the security inherent in such a residence. Furthermore, inlight of the parameters of control and entropy, the eastern quarter of the fort was found to exhibit the lowest level ofboth access and control across the fort. In terms of connectivity, Court I enjoyed the highest level of accessibility,continuity, and spatial coherence with the remaining spaces at the complex as they all clustered around this centralcourtyard. Court II showed the highest degree of integration. It was probably home to the administrative body,and perhaps also supplied the services to other quarters, as suggested by the passageways linking it to the differentparts of the fort.